The DeLone and McLean Model for Measuring Success Hospital Management Information System Case Study: Praya Regional Hospital - Kartini, Ajeng Mastuti; Fadli, Sofiansyah; Fahmi, Hairul; saikin, saikin (Universitas Trilogi, 2025)
The advancement of information technology in the health sector encourages hospitals to implement Hospital Management Information Systems (SIMRS) to improve efficiency, effectiveness, and service quality. This study aims to measure the success rate of SIMRS implementation at Praya Regional Hospital using the DeLone and McLean model, which includes six variables: system quality, information quality, service quality, usage, user satisfaction, and net benefits. Data was collected through distributing questionnaires to 101 respondents in all service units of RSUD Praya. The analysis was conducted using the Structural Equation Modeling-Partial Least Square (SEM-PLS) method. The results showed that only three of the nine hypotheses proposed proved significant, namely the effect of user satisfaction on net benefits, service quality on usage, and usage on net benefits. These findings indicate that technical aspects and system services need to be improved to achieve optimal SIMRS implementation. This research contributes to the evaluation of hospital information systems and can serve as a reference in making future system development decisions.